ECONOMIC SANCTIONS AGAINST THE ISLAMIC REPUBLIC OF IRAN FROM THE HUMAN RIGHTS PERSPECTIVE - Izadi, Arash (European Scientific Journal, ESJ, 2014)
Since the Islamic Revolution in 1979, Islamic Republic of Iran has always exposed to various international sanctions due to different reasons and excuses. They put Iran under different sanctions directly or indirectly through international organizations, under the pretext of creating an international order. As matter of fact, they pursue their own foreign policy goals and use sanctions as a means to achieve those goals. Economic sanctions is one of the sanctions type that have been imposed on Iran since the beginning of the revolution, And some of them involve deprivations and restrictions of Iranians which are against the basic and essential principles of human rights; although they are inapplicable based on International human rights documents and treaties, and their implementation is a crime and acts contrary to human rights. Governments cannot violate fundamental human rights and arrangements to humanitarian law with excuses of avoiding violation of international law and international order.